How to create and use rubrics for formative assessment and grading - Brookhart, Susan M. (ASCD, 2013)
What are rubrics and why are they important? -- Common misconceptions about rubrics -- Writing or selecting effective rubrics -- General rubrics for fundamental skills -- Task-specific rubrics and scoring schemes for special purposes -- Proficiency-based rubrics for standards-based grading -- Checklists and rating scales: not rubrics, but in the family -- More examples -- Rubrics and formative assessment: sharing learning targets with students -- Rubrics and formative assessment: feedback and student self-assessment -- How to use rubrics for grading.